Intrahospital supervised exercise training improves survival rate among hypertensive patients with COVID-19 - Fernandez, Francisco; Vazquez-Muñoz, Manuel; Canals, Andrea; Arce-Álvarez, Alexis; Salazar-Ardiles, Camila; Alvarez, Cristian; Ramirez-Campillo, Rodrigo; Millet, Gregoire P; Izquierdo, Mikel; Andrade, David C (Journal of applied physiology (1985), 2023)
Among the people most affected by coronavirus disease 2019 (COVID-19) are those suffering from hypertension (HTN). However, pharmacological therapies for HTN are ineffective against COVID-19 progression and severity. It has been proposed that exercise training (EX) could be used as post-COVID treatment, which does not rule out the possible effects during hospitalization for COVID-19. Therefore, we aimed to determine the impact of supervised EX on HTN patients with COVID-19 during hospitalization. Among a total of 1,508 hospitalized patients with COVID-19 (confirmed by PCR), 439 subjects were classified as having HTN and were divided into two groups: EX ( = 201) and control ( = 238) groups. EX (3-4 times/wk during all hospitalizations) consisted of aerobic exercises (15-45 min; i.e., walking); breathing exercises (10-15 min) (i.e., diaphragmatic breathing, pursed-lip breathing, active abdominal contraction); and musculoskeletal exercises (8-10 sets of 12-15 repetitions/wk; lifting dumbbells, standing up and sitting, lumbar stabilization). Our data revealed that the EX (clinician: patient, 1:1 ratio) intervention was able to improve survival rates among controlled HTN patients with COVID-19 during their hospitalization when compared with the control group (chi-squared: 4.83; hazard ratio: 1.8; 95% CI: 1.117 to 2.899; = 0.027). Multivariate logistic regression analysis revealed that EX was a prognostic marker (odds ratio: 0.449; 95% CI: 0.230-0.874; = 0.018) along with sex and invasive and noninvasive mechanical ventilation. Our data showed that an intrahospital supervised EX program reduced the mortality rate among patients with HTN suffering from COVID-19 during their hospitalization. In the present study, we found that exercise training improves the survival rate in hypertensive patients with COVID-19 during their hospitalization period. Our results provide strong evidence for the therapeutic efficacy of exercise training as a feasible approach to improving the outcomes of patients with COVID-19 who suffer from hypertension during their hospitalization.